(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Ensuring the national security of Kyrgyzstan integrally includes the protection of the spiritual and moral heritage, traditional norms and imperatives of public life. We are talking about protecting spiritual and moral security, allowing society to observe its vital parameters of ethical order within the limits of the historically established norm. Their going beyond traditional norms leads to the collapse of society as an integral system due to the destruction of the spiritual and moral foundations that structure it. The national interests of Kyrgyzstan in the field of spiritual life lie in the affirmation of the ideals of traditional morality, patriotism and humanism, and the development of centuries-old folk traditions. The article discusses the relevance of protecting spiritual and moral security in Kyrgyzstan.